2009
DOI: 10.1097/scs.0b013e3181c017fc
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Corticosteroid Treatment in Resolution of Bilateral Abducens Paralysis After Head Trauma

Abstract: A rare case of posttraumatic bilateral abducens palsy is presented. A 17-year-old male patient referred to our clinic because of complaints of diplopia, difficulty in opening his mouth, pain in the face, dyspnea, and chest pain after head trauma from a motor vehicle accident. The patient was not able to abduct eyes bilaterally, and diplopia occurred in the lateral gaze. All other extraocular movement was intact. He also had a mandibular fracture and bilateral pneumothorax. Computed tomography scan of the crani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In general, traumatic CNI is less likely to recuperate than cranial nerve impairment in the context of vascular disease [36]. In view of the therapeutic approach to ocular motor CNI, many methods of treatment including surgical correction, botulinum toxin injection, prisms, and steroid medication have been applied and reported apart from observation and watchful waiting [43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…In general, traumatic CNI is less likely to recuperate than cranial nerve impairment in the context of vascular disease [36]. In view of the therapeutic approach to ocular motor CNI, many methods of treatment including surgical correction, botulinum toxin injection, prisms, and steroid medication have been applied and reported apart from observation and watchful waiting [43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…10 As a result, steroids are often not given to patients with traumatic brain injuries with Glasgow coma score of 14 or less, which may often be the case in many patients with traumatic cranial nerve palsies. However, in patients with stable and reassuring neurological findings, the use of steroids has been described after traumatic CNIII, 11 traumatic abducens palsy, 12 and traumatic facial nerve palsy, 1 all generally with good results. Steroid use has also been described after presumed inflammatory CNIII palsy secondary to norovirus.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have demonstrated that, if given early enough, the steroids may limit the degree of inflammation and secondary damage to the endoneurium, and thus reduce the rate of aberrant regeneration. [11][12][13] Limitations of our study include its retrospective nature, small number of patients, variable or lacking steroid dosing regimens and timing, variable follow-up, and oculomotor measurements done without prism diopters. This study was not powered for statistical calculations, so no statement about statistical significance can be made.…”
Section: Discussionmentioning
confidence: 99%